Untreated chronic lymphocytic leukemia in Lebanese patients: an observational study using standard karyotyping and FISH. (December 2017) - Rassy, Elie El; Chebly, Alain; Korban, Rima; Semaan, Warde; Bakouny, Ziad; Assi, Tarek; Kourie, Hampig Raphael; Karak, Fadi El; Chouery, Eliane; Kattan, Joseph
Aim: We aimed to understand the biology of chronic lymphocytic leukemia (CLL) patients in Lebanon.Materials & methods: We applied conventional cytogenetic and FISH studies on Lebanese patients diagnosed with CLL and undergoing a watch and wait approach.Results: Our study disclosed 53.6% of patients with aberrant karyotypes among which 26.7% were complex karyotypes. Genetic aberrations included del(13q14) 46.4%, 14q32 translocation in 25%, trisomy 12 in 14.3%, del(17p13) and del(11q22) in 7.1% each. The deletion of 6q21/6q23 was not found in any of our patients.Conclusion: The higher prevalence of del(13q14) as a sole abnormality could be the primary event in inducing CLL. The del(17p13) and del(11q22) followed as potential drivers for progression in CLL patients with a watch and wait approach.